2013
DOI: 10.3171/2013.4.jns121919
|View full text |Cite|
|
Sign up to set email alerts
|

Attenuation of neurological injury with early baicalein treatment following subarachnoid hemorrhage in rats

Abstract: ObjectBaicalein has been shown to offer neuroprotection in the ischemic brain, but its effect in subarachnoid hemorrhage (SAH) is unknown. The authors used a double-hemorrhage model to study the role of early baicalein treatment in SAH.MethodsSubarachnoid hemorrhage was induced in male Wistar rats through a repeat injection of autologous blood at a 48-hour interval. Rats subjected or not subjected to SAH received a 30-mg/kg baicalein injection 3 hours after SAH and daily for 6 consecutive days, and results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Acute brain injury after SAH is emerging as the main cause of the poor prognosis after SAH. Many studies have demonstrated that alleviating acute brain injury after SAH via various pathways may effectively mitigate the neural damage caused by SAH [17]. Several studies have shown the neuroprotective effects of PROG in numerous animal injury models, including traumatic brain injury, spinal cord injury, and ischemic stroke [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Acute brain injury after SAH is emerging as the main cause of the poor prognosis after SAH. Many studies have demonstrated that alleviating acute brain injury after SAH via various pathways may effectively mitigate the neural damage caused by SAH [17]. Several studies have shown the neuroprotective effects of PROG in numerous animal injury models, including traumatic brain injury, spinal cord injury, and ischemic stroke [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, the main cause of oxidative stress following SAH is oxyhaemoglobin release from erythrocytes in the subarachnoid blood clot [33], [34]. The increased level of oxidative stress, which occurs in different brain cells including neurons, is accompanied by neuronal apoptosis after SAH [8], [35], [36]. Therefore, inhibiting oxidative stress-induced neuronal apoptosis is a critical intervention strategy in SAH, and a line of evidence demonstrated that many antioxidant treatment reduced apoptosis of neurons after SAH [13], [16], [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that free radicals generation and intrinsic antioxidant enzyme system deficiency both contribute to oxidative stress, followed by the inflammatory and cellular injury response in SAH [8,10,11,17,18]. In line with this, research concerning free radicals scavenge has shown that anti-oxidative agents may improve the outcome of SAH patients [19][20][21]. Therefore, anti-oxidative treatment using free radical scavengers has been supposed a promising treatment strategy in SAH patients.…”
Section: Introductionmentioning
confidence: 94%